A multi-speed Europe: is it viable? A stock-flow consistent approach - Jacques Mazier; Sebastian Valdecantos (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2015)
Based on the hypothesis that states that the underlying cause of the crisis in the euro area is a combination of exchange-rate misalignments with uncoordinated wage policies, we explore different exchange-rate arrangements that may help to reduce imbalances between surplus and deficit countries. These alternative configurations of the eurozone, which imply abandoning the common currency to a greater or a lesser extent, are tested with a theoretical four-country stock-flow consistent model. We find that although the different alternatives of a multi-speed Europe vary in their stability and macroeconomic effects, in all cases they produce better results compared to the one that has been observed since the introduction of the euro.
Keywords: E12; E61; E65; F37; 330; eurozone crisis; exchange-rate misalignments; multiple euros